Incidence of cisplatin-induced ototoxicity in adult cancer patients based on audiometric confirmation of patient self-report - Voruz, François; Vuilleumier, Aurélie; Migliorini, Denis; Nacher-Soler, German; Rousset, Francis; De Maesschalck, Thibault; Senn, Pascal (Frontiers in Audiology and Otology, 2023)
Robust clinically relevant epidemiological and audiological data are needed to prepare for future clinical trials aiming at preventing cisplatin-induced ototoxicity in this suffering cancer population. For this purpose, we retrospectively assessed the incidence, severity, and potential risk factors of symptomatic cisplatin-induced ototoxicity in a large cohort in a tertiary care hospital. Additionally, we performed a comprehensive MEDLINE literature search regarding cisplatin ototoxicity, selecting studies that incorporated baseline audiometry before the ototoxic treatment. The study group included consecutive adult patients over 18 years old treated with cisplatin-based chemotherapy without concomitant inner ear radiotherapy or other ototoxic medication. Every participant underwent baseline pretreatment audiometry and was asked for audiological symptoms (tinnitus or subjective hearing loss). Only if symptomatic, comparative standard audiometry (0.125 to 8 kHz) was performed. Ototoxicity was defined by a threshold shift ≥15 dB HL in at least one of the tested frequencies. A total of 401 cancer patients (59% males) with a mean age of 56 years (range 18-80) were included. 81 patients (20%) developed symptomatic hearing loss, predominantly affecting the high frequencies from 4 to 8 kHz. Among them, 49 (60%) experienced simultaneous tinnitus. None of the analyzed potential risk factors (age, sex, smoking, hypertension, diabetes, dyslipidemia, chemotherapeutic regimen, and cumulative cisplatin dose) was statistically correlated with hearing loss. In conclusion, at least 1 out of 5 patients treated with cisplatin developed audiological symptoms correlated with audiometric hearing loss within the 0.125 to 8 kHz range, for which new-onset tinnitus is a sensitive symptom. Not all audiological symptoms are accompanied by audiometric change. No predisposing factor could be identified. Standardized audiological monitoring before and during cisplatin-based chemotherapy allows quantitative assessment of early and objective signs of ototoxicity, offering to optimize anticancer therapy while minimizing morbidity in a multidisciplinary setting.